The effects of varied inquiry experiences on teacher and student questions and actions in STS classrooms - (:unkn) unknown (My University, 2005)
The purpose of this study was to examine how different inquiry experiences affect in-service science teachers' performance in terms of their questions and classroom actions. Teachers in a workshop experience proceeded through structured, guided, and full inquiry stations where materials to make foam were provided. Participants were 26 in-service science teachers who were enrolled in an 8-day workshop learning about science-technology-society (STS) approaches to teaching. Those who experienced full inquiry first resulted in more curiosity, more questions, and more unique experiments than at the other two stations. Success in guided inquiry was observed when the guidance was provided by more open-ended questions posed by the leader teachers. The study raises questions concerning the limitations on student thinking when in structured and guided laboratories that characterize traditional science teaching. An analysis of this study may contribute important direction and information for science teaching and learning and encourage more moves for STS successes. Copyright © 2005 Sage Publications.
Keywords: Curiosity; Inquiry; Real-world context; Science-technology-society; Teaching